(untitled) (Bangladesh Journal of Medical Education, 2025)
Introduction and Objective: Medical students’ mental health is currently an issue of concern for medical education worldwide. To observe how mental health can be influenced by students’ medical education was the objective explored in this qualitative study based on comparative focus groups. Methods: This survey was part of a longitudinal research among Brazilian medical students and this stage consisted of a focus group. Two groups were conducted based on academic performance criteria by graduation rates (25th and 75th percentiles). The authors reviewed focus group transcripts using techniques of qualitative content analysis and developed categories, supported by representative quotations. Results: Nineteen students participated in focus groups. Factors reported as positive for students’ mental health included the practice of physical activity, socialization and free time, which corroborates the biological, psychological and social dimensions presented by participants regarding the concept of mental health. However, the competitive academic environment, extensive curriculum and lack of social support from the medical school were highlighted as characteristics that negatively affect participants’ mental health. Students also highlighted emotional support, curriculum reform and investment in extracurricular projects as options for improving the mental health of future medical students. Academic performance did not seem to be a determining factor for medical students’ mental health. Conclusion: Medical students’ mental health is influenced by their medical school experiences, understood as necessary and inherent to the process of becoming physician. The findings of this study show the need for curriculum changes in the medical training process for good practices that reinforce good mental health. BJME, Volume-16, Issue-02, July 2025: 88-100